2011
DOI: 10.1021/ol201786q
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Enantioselective Synthesis of 3-Aminochroman Derivatives Through Ruthenium-Synphos Catalyzed Asymmetric Hydrogenation

Abstract: A highly enantioselective asymmetric hydrogenation of various trisubstituted enamides derived from chroman-3-ones promoted by cationic Ru-Synphos catalysts is reported. This atom-economical and clean method provides an efficient route to optically active 3-aminochroman derivatives, which are important pharmacophores found in numerous drug candidates, in high chemical yields and enantiomeric excesses up to 96%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Among the most successful reports, Ratovelomanana et al. published the synthesis of 3‐aminochromanes with enantioselectivities up to 96% using Ru‐diphosphine catalysts . A more recent report showed similar high enantioselectivities in the reduction of enamides derived from 2‐tetralones ( ee s up to 96%) and enamides derived from 3‐chromanones ( ee s in the range 94–98%), using a Rh‐diphosphine catalysts .…”
Section: Resultsmentioning
confidence: 99%
“…Among the most successful reports, Ratovelomanana et al. published the synthesis of 3‐aminochromanes with enantioselectivities up to 96% using Ru‐diphosphine catalysts . A more recent report showed similar high enantioselectivities in the reduction of enamides derived from 2‐tetralones ( ee s up to 96%) and enamides derived from 3‐chromanones ( ee s in the range 94–98%), using a Rh‐diphosphine catalysts .…”
Section: Resultsmentioning
confidence: 99%
“…We next extended the Ru‐catalyzed hydrogenation reaction of trisubstituted enamides to access oxygen‐containing heterocycles, such as chroman derivatives,14 which possess significant biological properties 15. Particularly, 3‐aminochroman scaffolds are numerous structural elements in clinical candidates for psychiatric disorders, such as the selective agonists at 5‐HT 1A receptors Robazaltan (NAD‐299)16 and Alnespirone (+)‐S20499 17.…”
Section: Asymmetric Hydrogenation (Ah)mentioning
confidence: 99%
“…7 In 2011, we reported an atom economical and clean process for the synthesis of 3-aminochroman derivatives through cationic Ru-SYNPHOS-catalysed enantioselective hydrogenation of trisubstituted enamides (scheme 2). 8 Initial experiments revealed that the nature of the amide moiety and the substitution pattern in the aromatic ring exerted influence on the stereocontrol, while hydrogen pressure and reaction temperature did not significantly affect the stereochemical outcome. For this process, polar solvents tend to provide higher enantioselectivities than non-polar ones, with methanol being the optimum.…”
Section: Ru-catalysed Asymmetric Hydrogenation Of Trisubstituted Enammentioning
confidence: 99%